Modulation of striatal projection systems by dopamine - Gerfen, Charles R. (2011)
The basal ganglia are a chain of subcortical nuclei that facilitate action selection. Striatal direct and indirect pathways form the functional backbone of the basal ganglia circuit. Twenty years ago it was proposed that the ability of the striatum to use the rise and fall of dopamine (DA) to control action selection was due to the segregation of D(1) and D(2) DA receptors in direct and indirect pathway spiny projection neurons. Although this sparked a debate, the evidence accumulated since clearly supports this model. In particular, recent advances in the means of marking neural circuits with optical or molecular reporters has revealed a clear-cut dichotomy between these two cell types at the molecular, anatomical and physiological levels. The contrast provided by these studies has provided new insights into how the striatum responds to fluctuations in DA signaling and how diseases that alter this signaling change striatal function.